Optimization of Biodegradation of Cypermethrin by Bacillus stercoris isolated from pesticide-polluted farm soil and analysis of the metabolic products using GC MS - Priya R. Sonawani,; Manjusha M. Kulkarni, (The Bioscan, 2025)
Pesticides are frequently used to control pests in residential gardens, veterinary clinics, and agricultural settings. Because of their widespread use, they increasingly pose greater dangers to human-associated non-targeted organisms. Cypermethrin is popularly used for controlling different pests in various stages of the development of crops. Excess use of it causes soil and water pollution, and this affects soil microflora and aquatic life, too. There are different methods available for cypermethrin removal from the environment, such as Physical and chemical methods, but most of them are time-consuming and very expensive. The goal of the current study is to isolate microorganisms from polluted soil that are resistant to high cypermethrin concentrations. To isolate the microorganisms, the enrichment culture method was employed. Bacteria that grow on minimum media with cypermethrin were eliminated and identified using their morphological and biochemical characteristics. According to phylogenetic analyses, one bacterial isolate (PRSB-1) belonging to Bacillus stercoris, along with four other bacterial isolates (PRS-1, PRS-2, PRS-3, PRSB-2) are from Pseudomonas, Klebsiella, Bacillus, and Lactobacillus spp. respectively. The optimum conditions required for the growth and degradation of pesticide were studied, and it was found that 40℃ temperature and 7 pH is most suitable for degradation. Isolated members of the genera Bacillus were utilised for more thorough deterioration investigations with GC-MS analysis. The results of the degradation study unequivocally show that in situ bioremediation is the optimum method for this organism.